Trends of Paediatric Nutrition in Developing Countries - R. Sutedjo (Indonesian Pediatric Society, 1974)
An infant born and reared in an ade-quate environment will obtain growthand development adequately and de-velop his genetic potentials to becomean adult member of his communityoptimally in quality.Such is in average the case in develo-ped countries.In developing countries, however, pro-bably infants of only 10 to 20% ofthe population could be categorizedas such.